2016
DOI: 10.1371/journal.pone.0162490
|View full text |Cite
|
Sign up to set email alerts
|

Extremes of Interferon-Stimulated Gene Expression Associate with Worse Outcomes in the Acute Respiratory Distress Syndrome

Abstract: Acute Respiratory Distress Syndrome (ARDS) severity may be influenced by heterogeneity of neutrophil activation. Interferon-stimulated genes (ISG) are a broad gene family induced by Type I interferons, often as a response to viral infections, which evokes extensive immunomodulation. We tested the hypothesis that over- or under-expression of immunomodulatory ISG by neutrophils is associated with worse clinical outcomes in patients with ARDS. Genome-wide transcriptional profiles of circulating neutrophils isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 76 publications
3
25
0
Order By: Relevance
“…Our data also confirm the presence of shared pathways with group A and GP7 enriched gene subsets, including many implicated in lung pathogenesis such as airway pathology, acute phase response signaling, and hepatic fibrosis. These findings are in line with current information on ARDS from the available curated literature genes [26,[45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our data also confirm the presence of shared pathways with group A and GP7 enriched gene subsets, including many implicated in lung pathogenesis such as airway pathology, acute phase response signaling, and hepatic fibrosis. These findings are in line with current information on ARDS from the available curated literature genes [26,[45][46][47][48][49][50].…”
Section: Discussionsupporting
confidence: 90%
“…A better understanding of these key temporal and topographic processes may contribute to advance diagnostic and prognostic biomarkers and effective therapies [7,[20][21][22]. Genome sequencing studies on ARDS have concentrated on identification of plasma biomarkers that may facilitate diagnosis of ARDS which could, in theory, improve clinical care, enhance our understanding of pathophysiology, and be used to enroll more homogeneous groups of patients in clinical trials of new therapies, increasing the likelihood of detecting a treatment effect [2,[23][24][25][26][27][28].…”
mentioning
confidence: 99%
“…It is appreciated that negative regulators of the IFN response are required to prevent extreme and prolonged immune responses, which are associated with poor disease outcomes after infection (80)(81)(82). ETV7 potentially contributes to the cumulative activities of negative IFN regulators to limit IFN responses during pathogen clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Beilharz et al (77) demonstrated that application of low doses of IFN-α reduces viral load, which to a certain degree led to attenuated disease progression, whereas high dose application of type I IFN contributed to morbidity (77). In line, high expression levels of ISGs have been shown to correlate to worse outcomes in ARDS patients (78). This observation corresponds to reports stating that the IFN threshold needed to induce antiviral ISGs-showing a beneficial effect in acute respiratory viral infection-is by at least 10-fold lower than the IFN dose necessary to trigger ISGs that show immunomodulatory, death-inducing, or anti-proliferative effects and thus can contribute to disease progression (79)(80)(81)(82).…”
Section: Ifns In Acute Respiratory Viral Infectionmentioning
confidence: 99%